Wdr5-mediated H3K4 methylation facilitates HSPC development via maintenance of genomic stability in zebrafish - Xiaohan Wang; Mengyao Liu; Yifan Zhang; Dongyuan Ma; Lu Wang; Feng Liu (Proceedings of the National Academy of Sciences, 2025)
During fetal stage, hematopoietic stem and progenitor cells (HSPCs) undergo rapid proliferation with a tight control of genomic stability. Although histone H3 lysine 4 (H3K4) methylation has been reported to stabilize the genome in proliferating cells, its specific role in HSPC development remains elusive. In this study, we demonstrated that tryptophan-aspartic acid (WD) repeat protein 5 (Wdr5)-mediated H3K4 methylation is crucial for maintaining genomic stability of proliferating HSPCs in zebrafish embryos. Loss of wdr5 led to a severe reduction of HSPC pool in the caudal hematopoietic tissue, accompanied with attenuated H3K4 methylation level and evident p53 -dependent apoptosis in the HSPCs. Mechanistically, Wdr5-mediated H3K4 methylation maintains genomic stability by inhibiting the formation of abnormal R-loops in the HSPCs, whereas accumulation of R-loops exacerbates DNA damage. Moreover, the absence of H3K4 trimethylation leads to an inactivated DNA damage response (DDR) pathway, which is deleterious to DNA damage repair and genomic stability. Subsequently, we found that DDR-associated genes, mutL homolog 1 and breast and ovarian cancer interacting helicase 1 , are important to ensure HSPC survival, likely by stabilizing their genome. In summary, these findings reveal that Wdr5-mediated H3K4 methylation is essential for HSPC development through tight control of R-loop accumulation and DDR-associated program to ensure genomic stability and survival of proliferating HSPCs.